How are physicians delivering palliative care? A population-based retrospective cohort study describing the mix of generalist and specialist palliative care models in the last year of life. (September 2018) - Brown, Catherine RL; Hsu, Amy T; Kendall, Claire; Marshall, Denise; Pereira, Jose; Prentice, Michelle; Rice, Jill; Seow, Hsien-Yeang; Smith, Glenys A; Ying, Irene; Tanuseputro, Peter
Background: To enable coordinated palliative care delivery, all clinicians should have basic palliative care skill sets ('generalist palliative care'). Specialists should have skills for managing complex and difficult cases ('specialist palliative care') and co-exist to support generalists through consultation care and transfer of care. Little information exists about the actual mixes of generalist and specialist palliative care. Aim: To describe the models of physician-based palliative care services delivered to patients in the last 12 months of life. Design: This is a population-based retrospective cohort study using linked health care administrative data. Setting/participants: Physicians providing palliative care services to a decedent cohort in Ontario, Canada. The decedent cohort consisted of all adults (18+ years) who died in Ontario, Canada between April 2011 and March 2015 ( n  = 361, 951). Results: We describe four major models of palliative care services: (1) 53.0% of decedents received no physician-based palliative care, (2) 21.2% received only generalist palliative care, (3) 14.7% received consultation palliative care (i.e. care from both specialists and generalists), and (4) 11.1% received only specialist palliative care. Among physicians providing palliative care ( n  = 11, 006), 95.3% had a generalist palliative care focus and 4.7% a specialist focus; 74.2% were trained as family physicians. Conclusion: We examined how often a coordinated palliative care model is delivered to a large decedent cohort and identified that few actually received consultation care. The majority of care, in both the palliative care generalist and specialist models, was delivered by family physicians. Further research should evaluate how different models of care impact patient outcomes and costs.